Potentiometric determination of total nitrogen in soils by flow injection analysis with a gas-diffusion unit - Ferreira, Alexandra M. R. (2011)
A flow injection analysis (FIA) system incorporating a gas-diffusion unit and a potentiometric detector was developed for the determination of total nitrogen in soil digests. The solutions obtained from the Kjeldahl digestion of the soil samples were injected in the FIA system where ammonium was converted into ammonia. This gas diffused through a gas-permeable membrane to a buffer acceptor stream, allowing the separation of the gas from the rest of the sample. Once in contact with the buffer solution, ammonia was reconverted into ammonium and finally led to a tubular ammonium ion-selective electrode constructed for this purpose. The potentiometric detector is a PVC tubular selective electrode without inner reference solution, and with the sensor system composed of monactin in Tris (2-ethylhexyl) phosphate. Good agreement was obtained between the results provided with the developed FIA system and those from the classical Kjeldahl distillation/titration step, with relative deviations between the 2 methods always < 5%. A sampling rate of 80 determinations/h was achieved with good reproducibility for consecutive injections of soil digests (coefficients of variation < 3%).